Az igazságügyi osztály létrejötte a felelős magyar minisztérium szervezésekor (1848/49, 1867) - Antal, Tamás (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
In the process of establishing the Hungarian Royal Ministry of Justice, the “first organization” actually happened twice: in 1848 and 1867. The former has its 175th anniversary in 2023, the latter had the 155th one in 2022 parallel with other ministries that were already in operation as departments in 1848. This particular duality will be presented in brief focusing on the work and leadership of such Hungarian statesmen as Ferenc Deák and Boldizsár Horvát and their talented contemporaries.